The Effects of Antidepressants and Quetiapine on Heart Rate Variability - Huang, W.-L.; Liao, S.-C.; Kuo, T. B. J.; Chang, L.-R.; Chen, T.-T.; Chen, I.-M.; Yang, C. C. H. (Pharmacopsychiatry, 2016)
Introduction: The autonomic effects of antidepressants and quetiapine on heart rate variability (HRV) are inconsistent based on past studies. The aim of this study was to explore their influence on the HRV of psychiatric patients without psychotic symptoms.Methods: A total of 94 patients with depression, anxiety, or somatic symptoms, were recruited into this study. Based on their medication, 4 groups were identified: the no antidepressant group (n=19), the SSRI group (using sertraline or escitalopram, n=53), the other antidepressants group (using venlafaxine or mirtazapine, n=9), and the augmentation group (AG, using an antidepressant+quetiapine, n=13). The HRV of the 4 groups were compared. The correlations between HRV and the medication(s) used were clarified.Results: Among the 4 groups, the AG had the lowest HRV with its total power (TP), very low frequency power (VLF) and low frequency power (LF) of HRV being significantly different from those of the other groups. Age and using quetiapine were found to be negatively correlated with TP, VLF and LF. With this study group, the autonomic effects of antidepressants were found not to be significant.Discussion: Among psychiatric patients without psychotic symptoms, quetiapine causes an overt decrease in HRV.
Keywords: heart rate variability; autonomic nervous system; antidepressants; quetiapine